Analysis of sperm chromatin packaging and reproductive biomarker to evaluate the consequence of advanced male age - Bibi, Riffat; Jahan, Sarwat; Kafeel Qureshi, Salma; Razak, Suhail; Afsar, Tayyaba; Almajwal, Ali; Kafeel Qureshi, Mashal; Hammadeh, Mohammad Eid; Amor, Houda (Frontiers in Endocrinology, 2023)
In this study, subfertile males from Pakistan with their semen parameters, sperm chromatin integrity, antioxidant enzyme levels, and reproductive hormone levels were assessed concerning their age. Data on the demographic characteristics of the 750 study participants, including their general health, body mass index (BMI) and reproductive status, were collected from subfertile men from Pakistan. Semen and blood were collected to determine standard semen parameters, sperm chromatin dispersion (Halosperm-SCD), sperm chromatin integrity using toluidine blue staining (TB), sperm chromatin maturity using chromomycin A3 staining-(CMA3+) and reproductive hormone (FSH, LH, prolactin and testosterone levels). The patients were divided into three groups according to their age: Group 1 included males aged 30 years or less (n=90), Group 2 included male subjects between the ages of 31 and 40 years (n=330), and Group 3 included male subjects over 40 years of age (n=330). Conventional semen parameters, reactive oxygen species (ROS), superoxide dismutase (SOD), guaiacol peroxidase (GPX), catalase (CAT), and lipid peroxidation (MDA) did not statistically (p>0.05) differ with increasing male age or between different age groups. When compared to younger men (<30 years) sperm SCD (23.2±0.88%) was significantly (p=0.01) lower as compared to males aged >40 years (26.6±0.6%). The concentration of LH, FSH and testosterone levels were comparable between the groups (p>0.05). While a significant (p=0.04) increase in sperm chromatin immaturity- CMA3+ (30±0.71%) was observed in the old age group (>40years) compared to the <30 years group (26.6±1.03%). A positive association was observed between advanced male age and sperm chromatin dispersion (SCD) (r=0.124, p=0.001) and decondensation (CMA3+) (r=0.1, p=0.009). Despite potential limitations, this study has been carried out with extensive information on the potential risk of male age on sperm integrity. The present study demonstrated the impact of male age on male reproductive health, as these patients had a higher percentage of sperm chromatin damage (SCD) in their semen. Sperm DNA damage assessment will help in the evaluation and diagnosis of the underlying cause of poor fertility and can help clinicians in selecting the right treatment options. Male age is one of factors that has an impact on the decline in male fertility,